1954
DOI: 10.1121/1.1927940
|View full text |Cite
|
Sign up to set email alerts
|

The Dispersion of Ultrasonic Pulse Velocity in Cylindrical Rods

Abstract: Velocity dispersion of compressional stress waves in cylindrical rods of 61S-T6 aluminum alloy has been investigated experimentally. Electronically generated pulses of the desired shape and carrier frequency were used to drive the barium titanate and quartz transducers. Both the pulse echo and pulse transmission methods were employed. It was found that the group velocity depends strongly on the ratio of a, the radius of the specimen, to λ, the wavelength of the stress disturbance, when the value of a/λ is less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1960
1960
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Silaeva and Shamina 5) found the limiting ratio of diameter to wavelength to be about 2 for metal rods. Tu et al 6) observed that the group velocity of compression waves depended on the ratio of the radius of a cylindrical aluminum-alloy rod to the wavelength when the value of the radius-to-wavelength ratio was less than 2.5.…”
mentioning
confidence: 99%
“…Silaeva and Shamina 5) found the limiting ratio of diameter to wavelength to be about 2 for metal rods. Tu et al 6) observed that the group velocity of compression waves depended on the ratio of the radius of a cylindrical aluminum-alloy rod to the wavelength when the value of the radius-to-wavelength ratio was less than 2.5.…”
mentioning
confidence: 99%